Terror films: The socio-cultural reconstruction of trauma in contemporary Israeli cinema - Ben-Moshe , Yael; Ebbrecht-Hartmann , Tobias (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Ben-Moshe Yael, Ebbrecht-Hartmann Tobias, Terror films: The socio-cultural reconstruction of trauma in contemporary Israeli cinema. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 69–86. ISSN 1731-450X. DOI 10.14746/i.2019.34.05. The public discourse in Israel regarding events such as the Holocaust, war, or terror attacks mostly failed to embrace the trauma caused by such events, and to integrate their effects in the collective memory. According to trauma theoreticians, the location of trauma in the discourse is related to the character of trauma as a non-narratable memory, since personal trauma exist in the void, thus marking a missing memory. This paper explores the notion of trauma in contemporary Israeli cinema as it was reconstructed during and after the Second Intifada (2000–2008). The paper focuses on feature films reflecting on experiences of terrorist violence, among them Avanim (2004), Distortion (2004), Frozen Days (2006), The Bubble (2006), 7 Minutes in Heaven (2009). These films embrace parallel elements structuring a worldview, in the private as well as the collective sphere, thus shaping the surroundings as a mirror of the self and the subjective traumatic experience as a reflection of a complex social reality. A particular focus of our analysis will also be on aesthetic strategies that cinematically express rupture and distortion of terrorist violence and trauma, especially moments of suddenness and disruption in contrast to duration and circular repetition, elements of a specific temporality of trauma that also shaped the narration and style of recent Israeli war films, such as Waltz with Bashir (2008) or Beaufort (2007).